2015
DOI: 10.1039/c5ra11387c
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Janus molecule for the facile preparation of water solutions of few layer graphene sheets

Abstract: A biobased Janus molecule was used to prepare water solutions of nano-stacks made by few layer graphene.The Janus molecule was 2-(2,5-dimethyl-1H-pyrrol-1-yl)-1,3-propanediol (serinol pyrrole, SP), a serinol derivative obtained through the neat reaction of 2-amino-1,3-propandiol with 2,5-hexanedione, with atom efficiency of about 85%. SP contains the pyrrole ring, suitable for the interaction with carbon allotropes and hydroxy groups, that can easily interact with polar surroundings. Adducts, with about 14% by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(83 citation statements)
references
References 80 publications
2
81
0
Order By: Relevance
“…At present, comparative investigation has not been performed. Some of the authors reported Raman spectra of HSAG [47]. In a Raman spectrum, lines D and G, located at 1350 and 1590 cm -1 respectively, indicate the presence of graphitic sp 2 -phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, comparative investigation has not been performed. Some of the authors reported Raman spectra of HSAG [47]. In a Raman spectrum, lines D and G, located at 1350 and 1590 cm -1 respectively, indicate the presence of graphitic sp 2 -phase.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest that sulphur addition occurs on the edges of HSAG graphene layers. Indeed, HSAG is characterized by the relevant presence of electronically perturbed edges [47], which could be suitable sites for the reaction with sulphur. Reaction was also performed between anthracene and sulphur, at 150°C for 12 hours (details are in the experimental part).…”
Section: Reactivity Of Sulphur With Carbon Allotropes and Hypothesis mentioning
confidence: 99%
“…Serinol pyrrole has been then used as the heterocyclic molecule for the functionalization of sp 2 carbon allotropes [20] and of graphene layers among them. Very high functionalization yield was reported and stable water dispersions of the carbon materials were obtained [21,22]. The high efficiency of the functionalization reaction paved the way to explore the reaction of the carbon allotropes with pyrrole compounds other than serinol pyrrole.…”
Section: Introductionmentioning
confidence: 99%
“…The polymeric nature of graphene layer with the six atoms aromatic ring as the repeating unit is responsible for such exceptional properties. Hence, main objectives of graphene synthesis [8][9][10][11][12] and functionalization [8,[13][14][15][16][17][18][19][20][21][22][23] are to obtain and preserve such structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, serinol chemoselectivity was exploited [32][33][34], preparing SP through the Paal-Knorr reaction [34,35] of serinol (S) with 2,5-hexanedione (HD), performing the reaction in the absence of solvents and catalysts. SP has been defined as a Janus molecule [36], that means a molecule with two faces and, hence, a dual reactivity. The Roman god Janus, represented (for example in coins) as having two faces in one body, inspired the definition 'Janus' first to describe micro-and nanoparticles with at least two physically or chemically differing surfaces [37,38] and then, more in general, molecules having two faces, a hydrophobic and a hydrophilic one, such as colloids [39] dendritic multiester [40], supermolecular liquid crystals [41], a binding protein for vitamin E [42], block copolymers with (meth)acrylic acid segments [43].…”
Section: Introductionmentioning
confidence: 99%